L'ennui ouvrier dans la pensée de Simone Weil. Cohérence du matériel et du spirituel - Bordes, Judith (Labyrinth, 2023)
This paper focuses on one aspect of Weil's philosophy of labor, which has not been studied until now: the problem of boredom. In a 1938 article, she defines boredom as the main source of suffering for factory-workers. But shouldn't boredom rather occur during leisure-time, when one has nothing to do? In fact, factory work can lead to boredom, despite its frenetic rhythm and the deep concentration it implies. According Weil, boredom in factory has two main causes: monotony, and the fact that, while working, the workers lose the control over their own time. This correlation of boredom with certain conditions of work is nowadays still relevant, and it concerns modern life not only in the working sphere. It implies a critical approach to the conditions of production in the capitalist era. But it also helps to describe the paradoxical state in which, while being active, one suffers from weariness. At last, it shows the relevance of an exploration of the various aspects of modern alienation through the problematic of time. The interest in the problem of boredom therefore allows to explore two complementary sides of Weil's thought: materialism and religious inspiration.